2022
DOI: 10.3390/ijms23179577
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal Capsazepine Administration Modulates Colonic Mucosal Health in Mice

Abstract: Antagonism of transient receptor potential vanniloid-1 (TRPV1) and desensitization of transient receptor potential ankyrin-1 (TRPA1) nociceptors alleviate inflammatory bowel diseases (IBD)-associated chronic pain. However, there is limited literature available about their role in regulating the mucosal layer, its interaction with host physiology, and luminal microbial community. The present study focuses on the effects’ intra rectal administration of capsazepine (modulator of TRPA1/TRPV1 expressing peptidergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…In the HFD + CPZ group, there was further increase in the intestinal permeability, suggesting that CPZ rectal treatment along with HFD aggravated the damage to gut barrier. This observation corroborates to our previous findings demonstrating detrimental outcomes of CPZ . Our previous studies have demonstrated that IMO supplementation improves HFD-induced alteration in intestinal permeability. , However, in the present study, no improvement in intestinal permeability was observed in the HFD + CPZ + IMO group.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the HFD + CPZ group, there was further increase in the intestinal permeability, suggesting that CPZ rectal treatment along with HFD aggravated the damage to gut barrier. This observation corroborates to our previous findings demonstrating detrimental outcomes of CPZ . Our previous studies have demonstrated that IMO supplementation improves HFD-induced alteration in intestinal permeability. , However, in the present study, no improvement in intestinal permeability was observed in the HFD + CPZ + IMO group.…”
Section: Discussionsupporting
confidence: 93%
“…Colon innervating TRPA1 and TRPV1 +ve peptidergic sensory neurons regulate intestinal pain during inflammatory conditions like IBD , and are crucial for colonic mucosal health. ,, Our group’s previous research demonstrated the functional role of TRPA1 and TRPV1 channels in the regulation of intestinal mucus homeostasis. ,, CPZ administration inhibits TRPA1- and TRPV1-mediated nociceptive response and has been proposed as a possible candidate for therapeutics for IBD . However, it also reduces gastrointestinal mucus production and alters gut barrier integrity, which contrasts to its protective effects. , HFD feeding has detrimental effects on glucose homeostasis, mucus content in the colon, and gut barrier integrity. ,, Hence, considering the clinical scenario, we studied how HFD consumption affects the colonic mucosal health of mucosal compromised patients (CPZ administered). Furthermore, the efficacy of prebiotics in these conditions was tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations